Medicago truncatula SOC1 Genes Are Up-regulated by Environmental Cues That Promote Flowering - Fudge, Jared B.; Lee, Robyn H.; Laurie, Rebecca E.; Mysore, Kirankumar S.; Wen, Jiangqi; Weller, James L.; Macknight, Richard C. (Frontiers in Plant Science, 2018)
Like Arabidopsis thaliana, the flowering of the legume Medicago truncatula is promoted by long day (LD) photoperiod and vernalization. However, there are differences in the molecular mechanisms involved, with orthologues of two key Arabidopsis thaliana regulators, FLOWERING LOCUS C (FLC) and CONSTANS (CO), being absent or not having a role in flowering time function in Medicago. In Arabidopsis, the MADS-box transcription factor gene, SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (AtSOC1), plays a key role in integrating the photoperiodic and vernalization pathways. In this study, we set out to investigate if the Medicago SOC1 genes play a role in regulating flowering time. Three Medicago SOC1 genes were identified and characterized (MtSOC1a-c). All three MtSOC1 genes, when heterologously expressed, were able to promote earlier flowering of the late-flowering Arabidopsis soc1-2 mutant. The three MtSOC1 genes have different patterns of expression. However, consistent with a potential role in flowering time regulation, all three MtSOC1 genes are expressed in the shoot apex and are up-regulated in the shoot apex of plants in response to LD photoperiods and vernalization. The up-regulation of MtSOC1 genes was reduced in Medicago fta1-1 mutants, indicating that they are downstream of MtFTa1. Insertion mutant alleles of Medicago soc1b do not flower late, suggestive of functional redundancy amongst Medicago SOC1 genes in promoting flowering.